A trend analysis of crimes in Bangladesh - Islam, Saima Sharleen; Haque, Md Samiul; Miah, M. Saef Ullah; Sarwar, Talha Bin; Bhowmik, Abhijit (Association for Computing Machinery, 2022)
This paper presents a trend analysis of crimes in Bangladesh based on the data provided by Bangladesh Police for the last ten years, from 2010 to 2019. The data contains the number of different crimes organized by the police units in different areas of Bangladesh. The aim of this work is to analyze the crimes committed in the last ten years, establish relationships between the different types of crimes, and identify patterns between them. In order to analyze the data, the dataset provided by Bangladesh Police is transformed into different forms, and then the correlation between different features is determined. The four most important features or crime types, namely murder, narcotics, smuggling, and dacoity, are analyzed in depth by analyzing the significance of the features. This study presents the overall scenario of the crime types and rates observed in the last decade and could be of great help to the law enforcement agencies to make future decisions based on the analysis presented in this paper.